Pregnancy outcomes among chronic carriers of hepatitis B virus - Sirinart Sirilert (2018)
Objective To compare pregnancy outcomes of women with chronic HBV infection with those of HBV-negative women. Methods A retrospective cohort study was undertaken to analyze singleton pregnancies of women without medical/surgical disease and with known HBsAg status. Pregnancy outcome measures were compared among the control group, women with positive HBsAg status (case group), and those with positive HBeAg status. Results Among 26 350 enrolled pregnant women, 21 812 in the control group and 1446 in the case group were compared. Only the proportion of preterm births was significantly higher among pregnancies with positive HBsAg status (RR 1.013 [95% CI, 1.001-1.025]). Among women with positive HBsAg status who had been screened for HBeAg, GDM was significantly higher among women with positive HBeAg status (RR 1.434 [95% CI, 0.999-2.057] ). Preterm births and low birth weight were also significantly higher among women with positive HBeAg status (RR 1.250 [95% CI, 1.000-1.563] and 1.258 [95% CI, 1.053-1.505] , respectively). Conclusion Chronic carriers of HBV had a minimally increased risk of preterm birth and low birth weight but the risk was more pronounced in women with positive HBeAg status. Women with positive HBeAg status also had an increased risk of GDM. © 2014 International Federation of Gynecology and Obstetrics.